Efeito de um extrato de Ganoderma lucidum (Reishi) na marcação de constituintes sanguíneos com tecnécio-99M e na sobrevivência de Escherichia coli - Agostinho, Raquel Terra (2009)
Clinical evaluations have been made possible with radiobiocomplexes marked with tecnecium-99m (99mTc). Natural or synthetic drugs are able to interfere in the marking of blood structures with 99m Tc. Also, the toxicity of several natural products has been described. The aim of this study was evaluating the effect of an extract of Ganoderma lucidum (Reishi) in the marking of blood constituents with 98m Tc and in the survival of Escherichia coli. Blood samples from Wistar rats were treated with reishi extract. Radiomarking procedure was performed. Samples of plasma (P), blood cells (CS), and insoluble (FI) and soluble (FS) fractions of P and CS were separated and the radioactivity was counted to determine radioactivity percentages (%ATI). Escherichia coli AB1157 cultures were treated with stannous chloride in the presence and absence of the reishi extract. Blood samples and bacterial cultures treated with NaCl 0.9% were used as controls. Data indicated that the reishi extract has significantly altered (p<0,05) the %ATI of P, CS, FI-P, FS-P, FI-CS e FS-CS, as well as it has increased survival of bacterial cultures treated with stannous chloride. Our results suggest that the Reishi extract would be able to present a redox/ chelant action by altering blood constituent marking with 99mTc and by protecting bacterial cultures against stannous chloride-induced oxydating lesions. The study had a multidisciplinary character, with the participation of the following areas of knowledge: Biophysics, Radiobiology, Botanics, Phytotherapy, and Hematology